The Predictive Role of Chinese English as a Foreign Language Teachers’ Psychological Capital in Their Job Commitment and Academic Optimism - Xu, Lihua; Zhu, Xiaowen (Frontiers in Psychology, 2022)
Positive psychology (PP) has received increasing attention in the field of education. Building upon PP, the current study set out to inspect the function of Chinese EFL teachers’ psychological capital in promoting their job commitment and academic optimism. To accomplish this, 316 Chinese teachers (i.e., 97 males, 219 females) were asked to complete “Psychological Capital Scale”, “Job Commitment Scale”, and “Academic Optimism Scale”. The results of regression analyses revealed that Chinese EFL teachers’ psychological capital can strongly predict their job commitment and academic optimism. The conclusion and implications of the results are finally discussed.